SEBARAN ANGKA KEMISKINAN YANG MENGAKIBATKAN KETIMPANGAN SOSIAL DI MASYARAKAT - Falah, Andrean; Amal, Muhammad Ichlasul; Lorenzo, Lorenzo (The Officium Nobile Journal, 2025)
The phenomenon revealed by this research indicates that the uneven distribution of poverty figures within society leads to wide social disparities, impacting the quality of life and individual opportunities in various aspects of life. When poverty is concentrated in specific areas or groups, access to vital resources such as education, healthcare, and infrastructure becomes uneven, causing difficulties in accessing viable economic opportunities. The aim of this research is to analyze the distribution of poverty and its impact on social inequality while highlighting the importance of geographical distribution in designing policies to reduce poverty and social disparities. The methodology employed in this study is legal research with a normative juridical approach, utilizing secondary data and applying descriptive-analytical methods. The research findings indicate that poverty can be understood in two main concepts: absolute and relative poverty, with measurements conducted by the Central Bureau of Statistics (BPS) using the basic needs approach and the Head Account Index. Structural poverty emerges as a major factor that is challenging to address, especially in regions with high population density such as Java and Bali. The uneven distribution of poverty can result in widespread social disparities, affecting the quality of life and individual opportunities in various aspects of life, thus necessitating a comprehensive approach to addressing social inequality.